REKREASI KULINER BETAWI DI MANGGA BESAR - Giovanni Gunawan; Franky Liauw (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Food is one of the basic survival needs. Indonesia is a country with a wide variety of cuisines. In Indonesia, food has become part of the culture. Unfortunately, there is a phenomenon, especially in big cities, where the younger generation prefers non-traditional culinary that gets rid of the position of traditional culinary. Culinary recreation is a lifestyle that has emerged recently. For people who like recreation, it's not complete if you haven't tried the specialties of a region. The food provided in each region also varies. The Betawi tribe is a pioneer of DKI Jakarta's cultural and cultural identity and the preservation of Betawi culinary culture will affect the community, both entrepreneurs and consumers. Metaphorical and experimental methods are taken as an approach in designing where the shape of the plate is taken as the basis for the shape of the building. The plates are then arranged horizontally, vertically, and with various inclinations to create a unique and interesting space experience. The existence of Betawi Culinary Recreation in Mangga Besar will bring many benefits for culinary connoisseurs and for the food industry in the Mangga Besar area, so that they can meet various culinary needs. As a result, Betawi food can be known by the wider community and help preserve Betawi food. Keywords:  Betawi; Culinary; Recreation AbstrakMakanan merupakan salah satu kebutuhan dasar untuk bertahan hidup. Indonesia merupakan negara yang beraneka ragam kulinernya. Di indonesia makanan sudah menjadi bagian dari budaya. Sayangnya muncul fenomena terutama di kota-kota besar dimana generasi muda lebih menyukai kuliner non-tradisional yang menyingkirkan posisi kuliner tradisional. Rekreasi kuliner merupakan gaya hidup yang mulai muncul belakangan ini. Bagi orang yang suka berekreasi, belum lengkap rasanya jika belum mencoba makanan khas suatu daerah. Makanan yang disediakan di tiap daerah juga bervariasi. Suku Betawi merupakan pelopor identitas budaya dan budaya DKI Jakarta dan pelestarian budaya kuliner Betawi akan mempengaruhi masyarakat baik pengusaha maupun konsumen. Metode metafora dan eksperimental diambil sebagai pendekatan dalam mendesain dimana bentuk piring diambil sebagai dasar bentuk bangunan. Piring kemudian disusun secara horizontal, vertikal, dan dengan kemiringan yang beragam untuk membuat pengalaman ruang yang unik dan menarik. Dengan adanya Rekreasi Kuliner Betawi di Mangga Besar akan membawa banyak manfaat bagi para penikmat kuliner dan bagi industri makanan di kawasan Mangga Besar, sehingga dapat memenuhi berbagai kebutuhan kuliner. Alhasil, makanan khas Betawi bisa dikenal masyarakat luas dan membantu melestarikan makanan Betawi.